Dysfunction of Cerebrovascular Endothelial Cells: Prelude to Vascular Dementia - Wang, Feixue; Cao, Yu; Ma, Lina; Pei, Hui; Rausch, Wolf Dieter; Li, Hao (Frontiers in Aging Neuroscience, 2018)
Vascular dementia (VaD) is the second most common type of dementia after Alzheimer’s disease (AD), characterized by progressive cognitive impairment, memory loss, and thinking or speech problems. VaD is usually caused by cerebrovascular disease, during which, cerebrovascular endothelial cells (CECs) are vulnerable. CEC dysfunction occurs before the onset of VaD and can eventually lead to dysregulation of cerebral blood flow and blood-brain barrier damage, followed by the activation of glia and inflammatory environment in the brain. White matter, neuronal axons, and synapses are compromised in this process, leading to cognitive impairment. The present review summarizes the mechanisms underlying CEC impairment during hypoperfusion and pathological role of CECs in VaD. Through the comprehensive examination and summarization, endothelial nitric oxide synthase (eNOS)/nitric oxide (NO) signaling pathway, Ras homolog gene family member A (RhoA) signaling pathway, and CEC-derived caveolin-1 (CAV-1) are proposed to serve as targets of new drugs for the treatment of VaD.